Thiamine deficiency in Gambian women of reproductive age - Bourassa, Megan W. (2022)
Funding Information: This research was funded by a grant from the Bill & Melinda Gates Foundation to the New York Academy of Sciences. We would like to thank Damon Parkington, Amanda McKillion, and Taba-sum Tabasum, who performed the ETKac measurements. K.S.J. and A.K. are supported by the National Institute for Health Research (NIHR) Cambridge Biomedical Research Centre (IS-BRC-1215-20014). The NIHR Cambridge Biomedical Research Centre is a partnership between Cambridge University Hospitals NHS Foundation Trust and the University of Cambridge, funded by the NIHR. The views expressed are those of the authors and not necessarily those of the NHS, NIHR, or UK Department of Health and Social Care.